(untitled) (Circe de clásicos y modernos, 2018)
Vergil’s Aeneid built a legendary past that allows the Roman understanding of the multicultural composition of their own society, the ethnicity of the different groups and their ancestry and participation in public life in Rome. Through ethnographic positive and negative vectors set up a historical memory that combines the known past with legendary elements. Vergil determines the place of ethnic emphasis in the historical process of formation of Italy under Roman rule and recognized in the present, here lies a retrospect and an act of memory on the Bellum Sociale.